Edoardo Weiss papers - Weiss, Edoardo, 1889-1970.
Correspondence, writings, and speeches relating chiefly to Weiss's role in the development of psychoanalytic theory and to his association with Sigmund Freud and Paul Federn. Subjects include agoraphobia, the death instinct, the ego, female homosexuality, and narcissism. Correspondents include Ernst Federn, Paul Federn, Sigmund Freud, Ernest Jones, Enrico Agostino Morselli, and Julius von Wagner-Jauregg.
Library of Congress Prints and Photographs Division.
Psychoanalyst and author. Died 1970.
Collection material in English, with French, German, and Italian.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Federn, Ernst -- Correspondence; Federn, Paul; Federn, Paul -- Correspondence; Freud, Sigmund, -- 1856-1939.; Freud, Sigmund, -- 1856-1939 -- Correspondence; Jones, Ernest, -- 1879-1958 -- Correspondence; Morselli, Enrico Agostino, -- 1852-1929 -- Correspondence; Wagner-Jauregg, Julius von, -- 1857- -- Correspondence; Agoraphobia; Death instinct; Ego (Psychology); Lesbianism; Narcissism; Psychoanalysis; Authors; Psychoanalysts